Switching to a Dual-Drug Regimen in HIV-Infected Patients Could Be Associated With Macrophage Activation? - Vassallo, Matteo; Durant, Jacques; Fabre, Roxane; Ticchioni, Michel; Lotte, Laurene; Sindt, Audrey; Puchois, Annick; De Monte, Anne; Cezar, Renaud; Corbeau, Pierre; Pradier, Christian (Frontiers in Medicine, 2021)
Objectives: The aim of this study was to evaluate the effect on immune activation of switching from a triple-drug to a dual-drug regimen in HIV-1 infected patients on successful combination antiretroviral treatment (cART). Immunadapt is a prospective study evaluating the impact of cART simplification on immune activation Methods: We prospectively collected blood samples in HIV-1 infected patients on stable and successful cART switching from triple to dual regimens as a simplifying strategy. We compared immune activation markers: high sensitivity CRP, IL-1, IL-6, IL-8, IP-10, MCP-1, TNF-alpha, soluble CD14 (sCD14), soluble CD163 (sCD163), lipopolysaccharide binding protein, and D-dimer before cART change and at least 6 months after the switch. Patients were stratified according to low or high risk factors of immune activation (low CD4 nadir, previous AIDS-defining condition or very-low-level viremia during follow-up) Results: From April 2019 to May 2020, 20 subjects were included (mean age 57 years, 25 years since HIV infection, CD4 666 cells/mm3, CD8 766 cells/mm3, CD4/CD8 0.94, CD4 nadir 326 cells/mm3, 15% with AIDS, 18 years on cART, 6 cART regimens received, current cART duration: 56 months). Fourteen patients were prescribed Dolutegravir + Rilpivirine and six received Dolutegravir + Lamivudine. After 6.9 months, a significant sCD163 increase (+25.5% vs +0.5%, p=0.02) was observed in Discussion: cART simplification in favor of dual therapy is associated with macrophage activation in patients at risk of immune activation despite sustained virological control. Risk factors should thus be considered before generalizing such strategies.